The mononuclear phagocyte system obscures the accurate diagnosis of infected joint replacements - Robert Manasherob; Shay I. Warren; Prerna Arora; Lyong Heo; Naomi L. Haddock; Ievgen Koliesnik; Diasuke Furukawa; Z. Ngalo Otieno-Ayayo; William J. Maloney; David W. Lowenberg; Stuart B. Goodman; Derek F. Amanatullah (Journal of Translational Medicine)
Abstract Introduction Diagnosing infected joint replacements relies heavily on assessing the neutrophil response to bacteria. Bacteria form biofilms on joint replacements. Biofilms are sessile bacterial communities encased in a protective extracellular matrix, making them notoriously difficult to culture, remarkably tolerant to antibiotics, and able to evade phagocytosis. Phagocytized bacteria dramatically alter cytokine production and compromise macrophage antigen presentation. We hypothesize that a subset of joint replacements have a dormant infection that suppresses the neutrophil response to bacteria but can be distinguished from uninfected joint replacements by the response of the mononuclear phagocyte system (MPS) within periarticular tissue, synovial fluid, and circulating plasma. Methods Single cell RNASeq transcriptomic and OLink proteomic profiling was performed on matched whole blood, synovial fluid, and periarticular tissue samples collected from 4 joint replacements with an active infection and 3 joint replacements without infection as well as 6 joint replacements with a prior infection deemed “infection-free” by the 2018 Musculoskeletal Infection Society criteria (follow-up of 26 ± 3 months). Results The MPS and neutrophil responses differ by infected state; the cellular distribution of the MPS response in the subset of joints with dormant infections resembled actively infected joints (p = 0.843, Chi-square test) but was significantly different from uninfected joints (p < 0.001, Chi-square test) despite the absence of systemic acute phase reactants and recruitment of neutrophils (p < 0.001, t-test). When compared to no infection, the cellular composition of dormant infection was distinct. There was reduction in classically activated M1 macrophages (p < 0.001, Fischer's test) and alternatively activated M2 macrophages coupled with an increase in classical monocytes (p < 0.001, Fischer’s test), myeloid dendritic cells (p < 0.001, Fischer’s test), regulatory T-cells (p < 0.001, Fischer’s test), natural killer cells (p = 0.009, Fischer’s test), and plasmacytoid dendritic cells (p = 0.005, Fischer’s test). Hierarchical cluster analysis and single-cell gene expression revealed that classically M1 and alternatively M2 activated macrophages as well as myeloid dendritic cells can independently distinguish the dormant and uninfected patient populations suggesting that a process that modulates neutrophil recruitment (C1QA, C1QB, LY86, SELL, CXCL5, CCL20, CD14, ITGAM), macrophage polarization (FOSB, JUN), immune checkpoint regulation (IFITM2, IFITM3, CST7, THBS1), and T-cell response (VISIG4, CD28, FYN, LAT2, FCGR3A, CD52) was occurring during dormant infection. Gene set variation analysis suggested that activation of the TNF (FDR < 0.01) and IL17 (FDR < 0.01) pathways may distinguish dormant infections from the active and uninfected populations, while an inactivation of neutrophil extracellular traps (NETs) may be involved in the lack of a clinical response to a dormant infection using established diagnostic criteria. Synovial inflammatory proteomics show an increase in synovial CXCL5 associated with dormant infection (p = 0.011, t-test), suggesting the establishment of a chronic inflammatory state by the MPS during a dormant infection involved in neutrophil inhibition. Plasma inflammatory proteomics also support a chronic inflammatory state (EGF, GZMN, FGF2, PTN, MMP12) during dormant infection that involves a reduction in neutrophil recruitment (CXCL5, p = 0.006, t-test), antigen presentation (LAMP3, p = 0.047, t-test), and T-cell function (CD28, p = 0.045, t-test; CD70, p = 0.002, t-test) that are also seen during the development of bacterial tolerance. Discussion All current diagnostic criteria assume each patient can mount the same neutrophil response to an implant-associated infection. However, the state of the MPS is of critical importance to accurate diagnosis of an implant-associated infection. A reduction in neutrophil recruitment and function mediated by the MPS may allow joint replacements with a dormant infection to be mischaracterized as uninfected, thus limiting the prognostic capabilities of all current diagnostic tests.